Konsep Dasar dan Strategi Pelayanan Prima (Service Excellent) Pada Indosat Ooredo - Agtovia Frimayasa (Universitas Bina Sarana Informatika, 2017)
This study aims to determine the excellent service (Service Excellent), strategies and learn the concept of Total Quality Service (TQS) on Indosat Ooredo telecommunication company. The research results show that Customer service Ooredo is giving full attention to its customers especially when asking complicated complaints. So it can be said that the attention given is very good